THE ERADICATION OF ILLITERACY WITH LIBATKANKU (LIHAT BACA TULISKAN DAN LAKUKAN) METHOD - Iah, Ariah (Universitas Djuanda, 2015)
Illiteracy according to Indonesian Dictionary is unable to read and write (Pusat Pembinaan Pengembangan Bahasa 1990). Eradication of illiteracy is an activity that helps illiterate people to be able to write and read. Illiteracy eradication was conducted in the village of Cipayung Girang district, Megamendung, Bogor. Illiteracy eradication is carried out as one of the community service performed for three months ie from April to the month of June 2015. The way teaching illiteracy eradication will be implemented by using LIBATKANKU (Lihat Baca Tuliskan dan Lakukan). The approach often used in adult learning is problem-centered approach. This approach directs the learning experience on the problems faced by the learning in everyday life. So that the implementation of the approach is to apply the things or words that correspond to the work of the participants are illiterate.